ANALYSIS OF COMMUNICATIVE COMPETENCE DEVELOPMENT IN FUTURE TEACHERS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the theoretical and methodological foundations for cultivating communicative competence in prospective teachers, its structural elements, and its relevance in pedagogical practice. In contemporary education, interpersonal communication is recognized as an essential component of a teacher’s professional competence, significantly influencing teaching quality, student motivation, and the psychological atmosphere of the classroom. The study also highlights effective pedagogical strategies for enhancing communicative skills, including communicative-empathic trainings, conflict management workshops, technical speech development exercises, as well as supervision and mentoring practices.This article explores the theoretical and methodological foundations for cultivating communicative competence in prospective teachers, its structural elements, and its relevance in pedagogical practice. In contemporary education, interpersonal communication is recognized as an essential component of a teacher’s professional competence, significantly influencing teaching quality, student motivation, and the psychological atmosphere of the classroom. The study also highlights effective pedagogical strategies for enhancing communicative skills, including communicative-empathic trainings, conflict management workshops, technical speech development exercises, as well as supervision and mentoring practices.